Enantio- and Diastereoselective Assembly of Multi-Layer Folding Chiral Targets via Asymmetric Catalytic Single C–C Bond Formation - Liu, Yangxue; Rouh, Hossein; Tang, Yao; Wu, Guanzhao; Yuan, Qingkai; Zhang, Sai; Wang, Jia-Yin; Jin, Shengzhou; Xu, Ting; Wang, Yu; Pan, Junyi; Unruh, Daniel; Li, Guigen (Synlett, 2022)
This work presents the first enantio- and diastereoselective assembly of multi-layer folding targets through asymmetric catalytic C–C bond formation. Pd[(S)-BINAP]Cl2 is found to be an efficient catalyst for the Suzuki–Miyaura coupling between phosphinyl bromides and benzothiadiazole boronic esters for this asymmetric assembly. The structure of the resulting chiral multi-layer folding framework is unambiguously determined by X-ray analysis and shows a nearly parallel pattern of three layers and quasi-syn and -anti configurations. Good to excellent diastereo- and enantioselectivities (up to >20:1 dr and >99:1 er) are achieved.
Keywords: folding chirality; multi-layer chirality; Suzuki–Miyaura coupling; chiral phosphine amide; phosphine oxide